Urban expansion impacts on agricultural land and thermal environment in Larkana, Pakistan - Rahman, Ghani; Chandio, Noor Hussain; Moazzam, Muhammad Farhan Ul; Al Ansari, Nadhir (Frontiers in Environmental Science, 2023)
Urban area expansion and increasing built-up area is a major threat to agriculture, natural environment and ecology throughout the world. The population of Larkana city is rapidly increasing due to natural growth and uncontrolled migration from the surrounding areas which have resulted haphazard increase in the built-up area over the fertile agricultural land and have affected the city thermal environment. This research aims to evaluate the impacts of urban area expansion on agricultural land and thermal environment of the study area through assessment of change in land use land cover (LULC) from 1990 to 2020 and land surface temperature (LST). For this purpose, the Random Forest (RF) algorithm has been applied and LST has been calculated in Google Earth Engine (GEE) using Landsat imageries for the years 1990, 2000, 2010 and 2020. For RF classifier algorithm, 3500 reference random points were generated for each year which were divided randomly into two datasets i.e., training samples consist of 70% points and validation dataset (30% points). After LULC classification, the results were validated for 1990, 2000, 2010 and 2020 and the accuracy were 88.3%, 89%, 90.01% and 90.8%, respectively. The study results showed that the built-up area increased from 12.31 Sq.Km to 43.83 Sq.Km while the barren land in the study region decreased from 56.51 Sq.Km to 11.62 Sq.Km. The agricultural land was 66.66 Sq.Km in 1990 which expanded to 101.38 Sq.Km which again decreased to 79.49 Sq.Km in 2020. The results also revealed that most of the urban expansion in the last decade (2010-2020) was mostly over the agricultural land. The urban thermal environment also showed a gradual increase in surface temperature which were recorded from the LST results. The LST results revealed that the maximum LST was 33.4 ̊C in 1990 which increased to 36.1 ̊C in 2020 and similarly the minimum LST was 25.1 ̊C which also increased to 26.6 ̊C in 2020. This study provides useful results for stakeholders to devise better policy and planning to control further haphazard urban expansion over the fertile agricultural land in the study area.